PENGUKURAN TIME STUDY PADA PROSES PRODUKSI CELANA JEANS DI KONVEKSI BLACK VIPER CIKIJING - Sukma, Roji; Whydiantoro (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Measurement of Time Study in the jeans production process at Cikijing Black Viper Convection. Seeing the importance of measuring every activity carried out by the company, an accurate measurement method is needed to be able to provide precise information on the time needed and the efficiency of the movements of each activity to produce products. One method used to measure the time of the activity used is the time study method. Time Study is a work measurement technique by collecting data based on the time needed to complete a job. The Time Study method is used to calculate the standard time value of a job. Some factors that influence the production process are environmental factors, there are no work procedures, confusing procedures, human factors do other work before the job is finished, work while chatting, lack discipline, and rush in doing the work. By determining the adjustment seen from the skills of workers in doing their jobs, and determine the looseness determined from several factors that exist in the work environment, as well as workers, it can be obtained standard time of the production process.